2002
DOI: 10.1007/s00432-002-0387-5
|View full text |Cite
|
Sign up to set email alerts
|

Profiling genes differentially expressed in NGX6 overexpressed nasopharyngeal carcinoma cells by cDNA array

Abstract: We demonstrated the existence of a panel of genes that can be regulated by NGX6. Overexpression of NGX6 can influence the distribution of the cell cycle in NPC cells. Further studies are necessary to elucidate the exact function of these genes and their relationship to NGX6 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Firstly, NGX6 gene may be involved in cell cycle regulation and play an important role in tumor growth suppression. Our previous studies showed that significant accumulation of cells in the G0-G1 fraction was observed in HNE 1 cell transfected with NGX6 gene by using flow cytometric analysis, and several genes related to cell cycle and transcription regulation were differentially expressed in NGX6 overexpressed nasopharyngeal carcinoma cells by cDNA array assay [34,35,40] . Combined with our data presented here, it is reasonable to speculate that deletion or down-regulation of NGX6 gene in colorectal cancer may contribute to tumor cell proliferation and tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, NGX6 gene may be involved in cell cycle regulation and play an important role in tumor growth suppression. Our previous studies showed that significant accumulation of cells in the G0-G1 fraction was observed in HNE 1 cell transfected with NGX6 gene by using flow cytometric analysis, and several genes related to cell cycle and transcription regulation were differentially expressed in NGX6 overexpressed nasopharyngeal carcinoma cells by cDNA array assay [34,35,40] . Combined with our data presented here, it is reasonable to speculate that deletion or down-regulation of NGX6 gene in colorectal cancer may contribute to tumor cell proliferation and tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Restoring the expression of NGX6 significantly decreased the invasion and metastasis of NPC, improved the gap junction communication between cells, and reversed the malignancy of NPC cells [157]. Further studies showed that NGX6 regulated K-RAS [158], MEK1, and JUN expression, inhibited the phosphorylation of EGFR and MAPK kinase activity, up-regulated the expression of adhesion molecules such as nm23 and cadherin α2, and interacted with the cytoskeletal protein ezrin [151,159]. NGX6 inhibited the cell cycle and cell proliferation through the EGFR/ras/MEK/MAPK pathway [144,160,161], and interacted with adhesion molecules to regulate the adhesion and migration of cells, altering the invasion and metastasis of the tumor [162].…”
Section: Important Genes In Npc Carcinogenesismentioning
confidence: 97%
“…NGX6b can bind to the cell membrane via an intracellular region with ezrin and inhibit the cell proliferation, cell invasion, and metastasis of nasopharyngeal carcinoma through the EGF receptor signaling pathway (12,13). NGX6b can also inhibit the invasion of colon cancer cells by inhibiting the Wnt/␤-catenin signaling pathway (4,5,14). The isoform NGX6a was recently found to be expressed in various organs, mainly in epithelial cells and neuronal cells in the brain, nasopharynx, and lung, whereas NGX6b is expressed in the brain, heart, kidney, nasopharynx, and lung, and the expression levels of NGX6a are much higher than are those of NGX6b (3).…”
mentioning
confidence: 99%
“…Our previous studies demonstrated that the NGX6 gene encodes a product of two isoforms, NGX6a and -b, from three different transcripts (2). NGX6b encodes 338 amino acids, which contain the extracellular domain of an EGF-like domain and two transmembrane domains, whereas NGX6a contains the extracellular domain of an EGF-like domain and seven transmembrane domains (3)(4)(5). NGX6b mRNA expression is reduced or absent in nasopharyngeal carcinoma and colon cancer and is associated with tumor metastasis (6 -9).…”
mentioning
confidence: 99%